Durian Pancake Training Boosts Business Potential Of Sumberpitu Msmes: Pelatihan Pancake Durian Dorong Potensi Usaha UMKM Sumberpitu - Firdasari , Aulia Vivi; Arifin , Muhammad Zainul; Hidayati, Nisfullaili; Najwa , Fauziatun; Ahfas , Akhmad (International Consortium of Education and Culture Research Studies, 2025)
General Background: Local agricultural commodities hold significant potential for driving rural economic development when processed into value-added products. Specific Background: Sumberpitu Village possesses abundant and high-quality durian resources; however, their utilization remains suboptimal, with limited efforts to transform them into marketable culinary innovations. Knowledge Gap: There is a lack of empirical studies exploring how locally sourced durian can be processed into innovative products that contribute to economic empowerment at the village level. Aims: This study aims to identify the potential of local durian in Sumberpitu Village and analyze the role of culinary innovation—specifically durian pancakes—in increasing the economic value of durian and supporting local livelihoods. Results: Employing a qualitative descriptive method, data were gathered through interviews, observations, and document analysis. The findings reveal that Sumberpitu’s durians are diverse and of high quality, providing a strong foundation for product development. Culinary innovations such as durian pancakes are identified as promising products with the potential to become signature items of the village. Novelty: This study presents a focused approach to rural development through culinary innovation by leveraging a specific local commodity, positioning it as a community-based entrepreneurship opportunity. Implications: Developing durian-based culinary products not only increases community income and generates employment but also strengthens the local economy by promoting village identity and food-based tourism. Thus, culinary innovation rooted in local resources emerges as a strategic tool for rural economic advancement. Keywords: Durian, Culinary Innovation, Sumberpitu Village, Rural Economy, UMKM Highlights: Durian pancakes have strong potential as a village signature product. Culinary innovation transforms local resources into economic value. Village identity is strengthened through food-based entrepreneurship.